THE BALKAN WARS AND THE FIRST WORLD WAR AS MOTIFS IN THE FOLK SONGS FROM STRUMICA AND STRUMICA REGION (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
Ivan Kotev is the biggest living contemporary collector of folk art, who in his five-decade search for the folklore treasure of Strumica and the region has collected extensive folklore-ethnographic material. The book “A terrible battle started up in the Balkans” (Macedonian folk songs from Strumica and Strumica area about the Balkan Wars and the First World War) is a rare book in Macedonian folklore that contains about forty folk songs with motifs from the Balkan Wars and the First World War. The literary-linguistic analysis of the folklore units included in the book give a clearer image of an important period of Macedonian history, about which the people sang the least. The poems are original records and variants of known motifs from an important historical epoch and during their detailed analysis, the linguistic features (especially lexical) of the vernacular from this area and its development over a period of almost fifty years are emphasized. Keywords: Folk song, Balkan Wars, World War I.